PROSEDUR DAN METODE PENERJEMAHAN ARTIKEL INGGRIS-INDONESIA “LOST IN TRANSLATION JAPAN” - Arif Bagus Prasetyo (Balai Bahasa Provinsi Papua, 2018)
AbstractThe study focuses on the translation procedures and method employed by the translator in translating the English source text into Indonesian. It examined the English-Indonesian article entitled “Lost in Translation Japan”. The data was collected from the Garuda Magazine by comparing Source-Target Languages. The collected data was analyzed by the translation procedures and methods. The translation procedures was proposed by Vinay and Darbelnet, the procedures proposed by Molina and Albir, and the methods proposed by Newmark, are used as an instrument to identify the translation techniques employed by the translator. The result showed that a number of procedures and methods were applied: Borrowing, Calque, Transposition, etc. AbstrakKajian ini fokus pada prosedur dan metode penerjemahan yang diterapkan oleh penerjemah dalam menerjemahkan teks sumber berbahasa Inggris ke dalam bahasa Indonesia.Teks yang dikaji adalah artikel bahasa Inggris-Indonesia berjudul “Lost in Translation Japan”. Data dikumpulkan dari Majalah maskapai Garuda Indonesia dengan membandingkan Bahasa Sumber dan Bahasa Sasaran. Data yang diperoleh kemudian dianalisa menggunakan prosedur dan metode penerjemahan.Prosedur penerjemahan yang digunakan sebagai instrumen untuk mengidentifikasi teknik penerjemahan yang diterapkan oleh penerjemah adalah prosedur dari Vinay and Darbelnet, Molina dan Albir, dan metode penerjemahan dari Newmark. Hasil kajian memperlihatkan bahwa sejumlah prosedur dan metode yang diterapkan adalah Peminjaman, Calque, Transposisi, dll.